Sustainable Finance as A Moral Objective: An Islamic Economic Philosophy Perspective On The Optimization Of Sharia Fintechsuhardi - Arif Rahman Hakim; Wahyu Amru Rofiqhoh; Nur siamah (Nomico, 2026)
Sustainable finance is frequently reduced to an instrument for risk management or compliance with Environmental, Social, and Governance (ESG) standards. This article seeks to reframe this perspective by positioning sustainable finance as a moral objective within the framework of Islamic economic philosophy, particularly in the development and optimization of Islamic Fintech. This study adopts a qualitative approach based on a literature review, employing the Foundation–Accelerator–Impact analytical framework. The findings indicate that Islamic Fintech does not merely serve to enhance efficiency and financial inclusion, but also represents the implementation of Maqashid Shariah values. At the foundational level, sustainable finance is grounded in the principles of Tawhid and Khilafah, which affirm humanity’s role as trustees in the management of resources. At the accelerator level, financial technology facilitates the advancement of social justice and equitable economic distribution. At the impact level, the digitalization of Islamic finance is directed toward preventing fasad, ensuring environmental sustainability, and strengthening distributive justice. Accordingly, the optimization of Islamic Fintech within the sustainable finance paradigm underscores the orientation of Islamic economics toward not only economic growth, but also the comprehensive realization of moral and ethical objectives.